A convex combination method for linear regression with interval data - Somsak Chanaim (2018)
© Springer International Publishing AG 2016. This paper introduces a new approach to fitting a linear regression model to interval-valued data by relaxing an assumption about using the center of interval data. We use convex combination between lower and upper values of the interval data as a parameter with value between [0,1]. Thus, the center method becomes a special case of this method. For the real application we use Capital Asset Pricing model (CAPM) and Autoregressive model (AR(p)) with interval-valued data to show that this method can provide a better result than the center method based on the Akaike information criterion (AIC).